Model Memproses Maklumat Perbezuan Individu Dan Implikasinya Kepada Pengajaran - Ng , Wai Kong (Penerbit Universiti Sains Malaysia, 1983)
The practice of instruction structured at the level of the "average learner" should be reviewed in the light of developments in individual differences research. Individual differences of learner in the areas fo general ability, individual traits, and cognitive styles are discussed. The InformationProcessing Models are used to provide explanations for differential achievement of learners, based on their individual personality characteristics, with differents instrustional methodologies, processed or procedures. The implications of individual difference studies and differential instructional strategies to educational psychology and educational technology are discussed with a view to further improve instruction and teaching-learning.